2000
DOI: 10.1016/s0092-8674(00)80838-7
|View full text |Cite
|
Sign up to set email alerts
|

Trio Combines with Dock to Regulate Pak Activity during Photoreceptor Axon Pathfinding in Drosophila

Abstract: Correct pathfinding by Drosophila photoreceptor axons requires recruitment of p21-activated kinase (Pak) to the membrane by the SH2-SH3 adaptor Dock. Here, we identify the guanine nucleotide exchange factor (GEF) Trio as another essential component in photoreceptor axon guidance. Regulated exchange activity of one of the two Trio GEF domains is critical for accurate pathfinding. This GEF domain activates Rac, which in turn activates Pak. Mutations in trio result in projection defects similar to those observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
255
0
6

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(280 citation statements)
references
References 50 publications
18
255
0
6
Order By: Relevance
“…Among other structural features, the Drosophila Trio contains a motif of DH-PH ± DH-PH tandem domains, the characteristic feature of GEFs speci®c for the Rho family GTPases. It was shown that Trio localizes at the growth cone membrane and that the trio mutant disrupted the photoreceptor axon projection patterns (Newsome et al, 2000), defects similar to those seen in both Pak and dock mutants (Garrity et al, 1996;Hing et al, 1999). This function of Trio in axon guidance depended upon its GEF activity, since mutation in one of two GEF domains of Trio completely abolished the Trio function.…”
Section: Nck Links Cell Surface Receptors To the Actin Cytoskeletonmentioning
confidence: 91%
See 1 more Smart Citation
“…Among other structural features, the Drosophila Trio contains a motif of DH-PH ± DH-PH tandem domains, the characteristic feature of GEFs speci®c for the Rho family GTPases. It was shown that Trio localizes at the growth cone membrane and that the trio mutant disrupted the photoreceptor axon projection patterns (Newsome et al, 2000), defects similar to those seen in both Pak and dock mutants (Garrity et al, 1996;Hing et al, 1999). This function of Trio in axon guidance depended upon its GEF activity, since mutation in one of two GEF domains of Trio completely abolished the Trio function.…”
Section: Nck Links Cell Surface Receptors To the Actin Cytoskeletonmentioning
confidence: 91%
“…This function of Trio in axon guidance depended upon its GEF activity, since mutation in one of two GEF domains of Trio completely abolished the Trio function. Newsome et al (2000) went on to identify the downstream signaling events activated by the Drosophila Trio, and showed that Trio activated Rac and Mtl (Mig-two-like), but not Cdc42 and Rho, which in turn bound Pak and induced membrane ru ing and lamellipodium formation. These results indicated that the Trio-Rac-Dock-Pak pathway functions in the control of growth cone guidance and motility.…”
Section: Nck Links Cell Surface Receptors To the Actin Cytoskeletonmentioning
confidence: 99%
“…Trio interacts with a receptor phosphatase, LAR, and potentiates the phenotype of LAR mutants (Bateman et al 2000). Trio also interacts with Dock to activate rac and PAK in photoreceptor axon guidance (Newsome et al 2000).…”
Section: Rho Gtpases: Organizers Of Actin Structuresmentioning
confidence: 99%
“…Recently Trio, a unique GEF that has binding domains for both Rac and Rho, has been studied in detail in Dro-sophila (Awasaki et al, 2000;Bateman et al, 2000;Liebl et al, 2000;Newsome et al, 2000). Trio activates Rac selectively by its GEF1 domain, and the GEF2 domain shows specificity for Rho (Debant et al, 1996).…”
Section: Balance Between Rac and Rhomentioning
confidence: 99%